Flirt - a dialogue between wearables and sculpture - Chee, Zhi Quan (2015)
Flirt is a project that provokes questions about the idea of romance. and re-formulating found in parades it allows flirting to become a modality of interaction. The work weaves together art, fashion and technology; the participants are invited to disguise themselves into characters via custom made garments and then to flirt with a mechanical and abstract rendering of an invented mate. This project draws on an artistic and exploratory connection between the participants and technology. It evolves into an experiential non-verbal dialogue between these entities.